2003
DOI: 10.1002/jbm.b.10058
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun nanofibrous polyurethane membrane as wound dressing

Abstract: Produced via electrospinning, polyurethane membrane, which has a unique property, has been of interest in medical fields. Electrospinning is a process by which nanofibers can be produced by an electrostatically driven jet of polymer solution. Electrospun fibers are collected in the form of membranes. The porous structured electrospun membrane is particularly important for its favorable properties: it exudates fluid from the wound, does not build up under the covering, and does not cause wound desiccation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
449
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 783 publications
(477 citation statements)
references
References 16 publications
3
449
0
9
Order By: Relevance
“…On the other hand, the small pore size of reported electrospun scaffolds has thus far shown to be difficult for ingrowth and migration of seeded cells. To date, electrospinning has been used for the fabrication of scaffolds from numerous biodegradable polymers, such as poly(ε-caprolactone) (PCL), poly(lactic acid) (PLA), poly(glycolic acid) (PGA), poly(lactide-co-glycolide) (PLGA) and polyurethane (PU); natural proteins have been used as well including collagen, elastin and gelatin [11,13,[17][18][19][20][21][22][23]. Gelatin is a natural protein derived from collagen by controlled hydrolysis and is a heterogeneous mixture of single-or multistranded polypeptides containing between 300 -4000 amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the small pore size of reported electrospun scaffolds has thus far shown to be difficult for ingrowth and migration of seeded cells. To date, electrospinning has been used for the fabrication of scaffolds from numerous biodegradable polymers, such as poly(ε-caprolactone) (PCL), poly(lactic acid) (PLA), poly(glycolic acid) (PGA), poly(lactide-co-glycolide) (PLGA) and polyurethane (PU); natural proteins have been used as well including collagen, elastin and gelatin [11,13,[17][18][19][20][21][22][23]. Gelatin is a natural protein derived from collagen by controlled hydrolysis and is a heterogeneous mixture of single-or multistranded polypeptides containing between 300 -4000 amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…(Perets et al, 2003). Furthermore, Khil et al have designed a type of porous chitosan scaffold, containing chitosan microspheres loaded with TGF-1, to enhance chondrogenesis (Khil et al, 2003). They demonstrated that the scaffolds containing the loaded chitosan microspheres significantly increased the cell proliferation and production of ECM.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have investigated the woundhealing properties of mats of electrospun type I collagen fibers on wounds in mice and they found that healing of the wounds was better with the nanofiber mats than with conventional wound care, especially in the early stages of the healing process 21, 45,59,[62][63][64] . Apart from electrospun collagen, silk, polyurethane, polycaprolactone fiber are also frequently used in wound dressing 14,60 . Jia et al have prepared non-woven antibacterial poly (vinyl alcohol) (PVA) membrane by electrospinning of PVA aqueous solution with addition of Ag+-loaded Zirconium phosphate nanoparticles for potential use in wound healing materials and antimicrobial tests proved the efficacy of nanoparticles containing nanofibers against tested strains 65 .…”
Section: Wound Dressingmentioning
confidence: 99%
“…For examples, nanofibrous scaffolds have been demonstrated as suitable substrates for tissue engineering 6-9 , immobilized enzymes and catalyst [10][11][12][13] , wound dressing [14][15] and artificial blood vessels [16][17] . They have also been used as barriers for the prevention of post-operative induced adhesion [18][19] and vehicles for controlled drug (gene) delivery [20][21][22][23][24] .…”
mentioning
confidence: 99%